The revenge list - McKinnon, Hannah Mary (Mira, 2023)
Accidentally leaving a list of people she wants to forgive in an Uber, Frankie Morgan, attending anger management therapy, thinks nothing of it until the first three people on the list die, causing her to fear for her life because the next name on the list is hers.